Caring Cancer Patients While Living With COVID-19: An Experience of a Tertiary Cancer Care Center - Shrestha, Murari Man; Dhakal, Hari Prasad; Gurung, Banita; Rajbhandary, Sajin; Shakya, Sachin; Shrestha, Ranish; Gurung, Sumitra; Sharma, Bishwash; Bhasinka, Lahar Maya; Tuladhar, Sampurna; et al. (Nepalese Journal of Cancer, 2020)
COVID-19 has emerged as a serious public health crisis of 21st century affecting millions of people around the world. First identified in Wuhan China, COVID-19 has spread globally claiming millions of human life and suffering. The Government of Nepal (GoN) has accelerated control measures through mass media, laboratory testing, quarantine, isolation and treatment of COVID patients in designated hospitals. With rapid spread of COVID-19, the government owned as well as the private hospitals and health institutions across the nation face a great challenge to contain the spread of the novel virus. Nepal Cancer Hospital and Research Center (NCHRC) has been managing uninterrupted treatment services to cancer patients since the beginning of spread of COVID-19 in Nepal. Early planning and preparedness has been crucial to ensure patient care in the midst of COVID-19 pandemic.